Transparansi dan Akuntabilitas Pengelolaan Keuangan Dana Desa untuk Mendorong Kemandirian Masyarakat Pedesaan - Gayatri, Gayatri; Latrini, Made Yeni; Widhiyani, Ni Luh Sari (Jurnal Ekonomi Kuantitatif Terapan; 2017: Vol. 10, No. 2, Agustus 2017 (pp. 110 - 252), 2017)
This study aims to determine the relation between the application of transparency and accountability on village fund allocation management. The accountability applied as a way to incarnate better governance, from its planning, execution, reporting, and accountability. We uses primary data gained from questionaires and documentations. We analyze the data using descriptive statistics and tau kendall correlations. The result suggests that there are strong relations between apllication of transparency and accountability  toward the management of village funding.
Keywords: Akuntabilitas, dan keuangan dana desa